2018
DOI: 10.1080/15384101.2018.1515549
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB/let-7f-5p/IL-10 pathway involves in wear particle-induced osteolysis by inducing M1 macrophage polarization

Abstract: NF-κB signaling pathway shows significant influence on wear particle-induced osteolysis, and this study aims to explore the underlying mechanism and the role of let-7f-5p in this process. A mouse calvarial osteolysis model was constructed with PMMA particles, and the bone marrow-derived macrophages (BMMs) were isolated from the osteolysis area. The expression of miRNA and protein was determined by qRT-PCR and western blot, respectively. The level of cytokines was evaluated with ELISA. Recombinant plasmids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…NF-κB is considered to be a member of pro-inflammatory family of main transcription factors in inflammatory processes. It participates in M1 macrophage polarization induced by various stimulations (Gao et al, 2018;Genard et al, 2018). Consistent with their reports, our data demonstrate that NF-κB pathway activation is associated with TWIST1 expression and M1 polarization in response to S. aureus infection.…”
Section: Discussionsupporting
confidence: 92%
“…NF-κB is considered to be a member of pro-inflammatory family of main transcription factors in inflammatory processes. It participates in M1 macrophage polarization induced by various stimulations (Gao et al, 2018;Genard et al, 2018). Consistent with their reports, our data demonstrate that NF-κB pathway activation is associated with TWIST1 expression and M1 polarization in response to S. aureus infection.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that TARBP2 increases the expression of let-7f-5p in OS cells, suggesting that TARBP2 may promote the maturation of pre-let-7f in these cells. The let-7f-5p miRNA is a member of the let-7 family, which is involved in cell growth, migration, invasion, and angiogenesis in tumors [15][16][17]. In the present study, we showed that let-7f-5p targeted TARBP2, suggesting there was a regulatory feedback loop between let-7f-5p and TARBP2.…”
Section: Micrornas (Mirnas) Are a Class Of Non-codingsupporting
confidence: 53%
“…In the present study, we focused on let-7f-5p, which is located at 9q22.3 and is a member of let-7 family. let-7f has been shown to play an important role in cell growth, migration, invasion, and angiogenesis in tumors [15,16]. However, the molecular mechanism by which let-7f-5p regulates OS cell proliferation and invasion remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Because NF-κB pathways play an essential role in M1 macrophage polarization,27 our research investigated its impact on NF-κB stimulation. Phosphorylation of p65 as well as IκB kinase (IKK) was noticeably increased in SIRT1-transfected macrophages compared to vector-transfected macrophages after LPS+ IFN-γ treatment (Figure 5).…”
Section: Resultsmentioning
confidence: 99%